2021
DOI: 10.3390/su132413746
|View full text |Cite
|
Sign up to set email alerts
|

Research on Substation Project Cost Prediction Based on Sparrow Search Algorithm Optimized BP Neural Network

Abstract: The prediction of power grid engineering cost is the basis of fine management of power grid engineering, and accurate prediction of substation engineering cost can effectively ensure the fine operation of engineering funds. With the continuous expansion of the engineering system, the influencing factors and data dimensions of substation project investment are gradually diversified and complex, which further increases the uncertainty and complexity of substation project cost. Based on the concept of substation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Among them, the support vector machine (SVM) [8] , association rule analysis [9] , cluster analysis [10] and other algorithms in descriptive mining can deeply mine the changing trend of construction cost, accurately estimate the relationship between construction cost and influencing factors and have strong generalization ability, which becomes the main tool of construction cost prediction. For example, Xu et al [11] used sparrow search algorithm and SVM to predict the project cost, and estimated the project cost by taking the actual project as a power grid case. Miao et al [12] put forward a rapid prediction system of engineering cost based on SVM model, which can achieve the purpose of rapid prediction of engineering cost through simple and interactive input of engineering features.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the support vector machine (SVM) [8] , association rule analysis [9] , cluster analysis [10] and other algorithms in descriptive mining can deeply mine the changing trend of construction cost, accurately estimate the relationship between construction cost and influencing factors and have strong generalization ability, which becomes the main tool of construction cost prediction. For example, Xu et al [11] used sparrow search algorithm and SVM to predict the project cost, and estimated the project cost by taking the actual project as a power grid case. Miao et al [12] put forward a rapid prediction system of engineering cost based on SVM model, which can achieve the purpose of rapid prediction of engineering cost through simple and interactive input of engineering features.…”
Section: Introductionmentioning
confidence: 99%
“…SSA was inspired by the foraging behavior and anti-predation behavior of sparrows ( 51 ) and has been applied to solve many complex engineering optimization problems ( 52 55 ). A brief description of SSA is as follows.…”
Section: Methodsmentioning
confidence: 99%
“…It can simulate the information transmission mode of human brain neurons, perform non-linear transformation and regression processing on complex information variables, and obtain operation results with a high fitting degree. The structure of the BP neural network consists of three layers: input layer, hidden layer, and output layer ( 52 ). The number of hidden layers is not fixed, it can be one layer or multiple layers.…”
Section: Methodsmentioning
confidence: 99%
“…In Xu et al [ 97 ], the SSA algorithm was used to optimize the BP Neural Network parameters to improve the prediction accuracy of the power gride engineering cost. The results showed that the proposed model SSA-BP was a practical solution for such a problem.…”
Section: Recent Variants Of Ssamentioning
confidence: 99%